(untitled) (Conferencea, 2024)
Intelligence activity is an important branch of ensuring the national security of the state. It is carried out in relation to foreign states and its purpose is to pursue the interests of one’s own state in the international arena, as well as to identify threats coming from foreign countries, timely inform the authorities and assess risks for planning preventive measures. Intelligence propaganda is used as one of the important tools in intelligence activities. The government, diplomatic sources, political parties, non-governmental sector, authoritative persons, spy apparatus are the important forces of this process. As for the important means of intelligence propaganda, mass media and social networks deserve special attention. Accordingly, intelligence propaganda can be used to strengthen the national security of one’s own state, at the expense of damaging the national interests of foreign countries.